Clinical management and mortality risk in those with eating disorders and self-harm: e-cohort study using the SAIL databank. Issue 2 (19th March 2021) - John, Ann; Marchant, Amanda; Demmler, Joanne; Tan, Jacinta; DelPozo-Banos, Marcos
Abstract : Background: Individuals with eating disorders who self-harm are a vulnerable group characterised by greater pathology and poorer outcomes. Aims: To explore healthcare utilisation and mortality in those with a record of: self-harm only; eating disorders only; and both co-occurring. Method: We conducted a retrospective whole population e-cohort study of individuals aged 10–64 years from 2003 to 2016. Individuals were divided into: record of self-harm only; eating disorders only; both self-harm and eating disorders; and no record of self-harm or eating disorders. We used linked routinely collected healthcare data across primary care, emergency departments, hospital admissions and out-patient appointments to examine healthcare contacts and mortality. Results: We identified 82 627 individuals: n = 75 165 with self-harm only; n = 5786 with eating disorders only; n = 1676 with both combined. Across all groups and settings significantly more individuals attended with significantly more contacts than the rest of the population. The combined group had the highest number of contacts per person (general practitioner, incident rate ratio IRR = 3.3, 95% CI 3.1–3.5; emergency department, IRR = 5.2, 95% CI 4.7–5.8; hospital admission, IRR = 5.2, 95% CI 4.5–6.0; out-patients, IRR = 3.9, 95% CI 3.5–4.4). Standardised mortality ratios showed the highest excess mortality overall in the self-harm only group (SMR = 3.2, 95% CI 3.1–3.3), particularly for unnatural causes of death (SMR = 17.1, 95% CI 16.3–17.9). SMRs and years of life lost showed an increased risk of mortality in younger age groups in the combined group. Adjusted hazard ratios showed increased mortality across all groups (self-harm only, HR = 5.3, 95% CI 5.2–5.5; eating disorders only, HR = 4.1, 95% CI 3.4–4.9; combined group, HR = 6.8, 95% CI 5.4–8.6). Conclusions: Individuals in all groups had higher healthcare service utilisation than the general population. The increased mortality risk in young people with a record of both eating disorders and self-harm highlights the need for early specialist intervention and enhanced support.